Does transportation vulnerability explain the relationship between changes in exposure to segregation and youth cardiovascular health?. (May 2019) - D'Agostino, Emily M.; Patel, Hersila H.; Hansen, Eric; Mathew, M. Sunil; Nardi, Maria I.; Messiah, Sarah E.
Abstract: Transportation vulnerability (lack of community/personal access to transportation that in turn increases the risk for health or financial consequences in the event of hardship/disease/disasters) may be an important mechanistic factor linking residential segregation to youth cardiovascular health inequities. This natural experiment examined the impact of transportation vulnerability on the association between changes in exposure to residential segregation and cardiovascular health among minority youth (n = 2, 129, mean age 9.1 years, 54% male; 52% Hispanic, 48% non-Hispanic black [NHB]; 49% high area poverty) over two years. Two-level generalized linear mixed models with random intercepts were fit to test the effects of transportation vulnerability on the association between changes in segregation and cardiovascular health (body mass index percentile (BMIP), sum of skinfold thicknesses, 400 m run time, systolic and diastolic blood pressure percentiles (SBPP and DBPP, respectively) over two school years and across gender. After adjusting for potential confounders (individual-level race/ethnicity, age, time, and park-area poverty), improvements in cardiovascular health were greatest for girls exposed to reduced segregation with high compared with low transportation vulnerability for all outcomes. Specifically, BMIP and SBPP decreased 29% (IRR 95% CI: 0.69, 0.73) and 13% (IRR 95% CI: 0.85, 0.90) vs. 10% (IRR 95% CI: 0.84, 0.96) and no significant change (IRR 95% CI: 0.88, 1.00), for high and low transportation vulnerability, respectively. Adjusted models showed the greatest improvements in cardiovascular health for boys exposed to reduced segregation and low compared with high transportation vulnerability for BMIP and skinfold thicknesses. Specifically, BMIP and skinfold thicknesses decreased 33% (IRR 95% CI: 0.73, 0.81) and 21% (IRR 95% CI: 0.74, 0.84) vs. increased 8% (IRR 95% CI: 1.05, 1.11) and no significant change (IRR 95% CI: 0.96, 1.03), for low and high transportation vulnerability, respectively. Policy interventions that promote transportation equity should be further studied as a means to reduce youth cardiovascular health disparities, particularly for girls living in areas with high racial/ethnic segregation. Highlights: Minority youth had more improved cardiovascular health in integrated areas. Girls with high transportation vulnerability and reduced exposure to segregation had the most improved cardiovascular health. Increasing transportation equity may promote youth cardiovascular health. Policy targeting transportation systems may reduce health inequities related to residential segregation.